2011
DOI: 10.1051/0004-6361/201117686
|View full text |Cite
|
Sign up to set email alerts
|

PKS 1814-637: a powerful radio-loud AGN in a disk galaxy

Abstract: We present a detailed study of PKS 1814-637, a rare case of powerful radio source (P 5 GHz = 4.1 × 10 25 W Hz −1 ) hosted by a disk galaxy. Optical images have been used to model the host galaxy morphology confirming it to be dominated by a strong (and warped) disk component that is observed close to edge-on to the line of sight. This is the first radio galaxy found to reside in a disk dominated galaxy with radio luminosity equivalent to powerful FRII objects. At radio wavelengths, PKS 1814-637 is about 480 pc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 65 publications
(99 reference statements)
3
72
0
Order By: Relevance
“…Therefore it is possible that CSS/HERGs are also hosted in disk galaxies, as NLS1s. An example of a disk host for a powerful CSS was found by Morganti et al (2011). Moreover in a very large sample of AGN, Best & Heckman (2012) found that HERGs host galaxies have different properties than those of LERGs and, in particular, these authors found that they are bluer with lower mass, lower 4000 Å break, and a higher star formation rate.…”
Section: Host Galaxymentioning
confidence: 96%
“…Therefore it is possible that CSS/HERGs are also hosted in disk galaxies, as NLS1s. An example of a disk host for a powerful CSS was found by Morganti et al (2011). Moreover in a very large sample of AGN, Best & Heckman (2012) found that HERGs host galaxies have different properties than those of LERGs and, in particular, these authors found that they are bluer with lower mass, lower 4000 Å break, and a higher star formation rate.…”
Section: Host Galaxymentioning
confidence: 96%
“…systems (e.g., Ledlow et al 1998;Hota et al 2011;Morganti et al 2011;Bagchi et al 2014;Kaviraj et al 2015;Mao et al 2015;Singh et al 2015), and among them, PKS 2004-447 is the only gamma-ray-emitting radio galaxy in which a disky pseudobulge and a stellar bar have been found. Since there is solid observational evidence pointing to the presence of fully developed relativistic jets emanating from PKS2004-447 Schulz et al 2016), it arises that the same spinning black hole conditions that enable the production of prominent relativistic jets can be met, even if non-major merger related black hole fueling mechanisms have ignited the AGN.…”
Section: (∼7×10mentioning
confidence: 99%
“…Powerful radio sources that are hosted by spiral and disk-dominated galaxies are known to exist at lowredshift, although to-date there are only a few tens of examples (e.g Morganti et al 2011), most of which are hosted by disk-dominated or lenticular galaxies (e.g. NGC612, Ekers et al 1978).…”
Section: Radio Galaxies That Are Hosted By Spiralsmentioning
confidence: 99%